Balinese Cuisine as an instrument in Driving Gastrodiplomacy in Australia - Rumadana, I Made Rumadana; Winata, Gede Adi Sistha (International Journal Labs, 2025)
This study investigates the potential of Balinese cuisine—specifically Ayam Betutu and Sate Lilit Ikan—as instruments for advancing Indonesia’s gastrodiplomacy efforts in Australia, particularly within the framework of the